2009
DOI: 10.1021/jf8034379
|View full text |Cite
|
Sign up to set email alerts
|

Saline Water Irrigation Effects on Fruit Development, Quality, and Phenolic Composition of Virgin Olive Oils, Cv. Chemlali

Abstract: Field-grown olive trees (cv. Chemlali) were used over two growing seasons to determine the effect of different saline water irrigation levels on fruit development characteristics, yield, and virgin olive oil (VOO) quality. The plants were irrigated with fresh water (FW; ECe=1.2 dS m(-1)) and saline water (SS; ECe=7.5 dS m(-1)). Fruit weight, olive, and oil content decreased under irrigation with saline water. Total oil contents were 27.85 and 25.7% fresh weight (fw) during 2005 in FW and SS irrigated plants, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 32 publications
3
33
1
Order By: Relevance
“…However, Dabbou et al (2010) reported an increase of the total amount of phenols associated with the increase in irrigation for Arbequina olive cultivar under Tunisian conditions. The phenol content was very low compared with values reported by Ben Ahmed et al (2009) in the same region, which could be attributed to harvest period, crop load and procedure of oil extraction.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…However, Dabbou et al (2010) reported an increase of the total amount of phenols associated with the increase in irrigation for Arbequina olive cultivar under Tunisian conditions. The phenol content was very low compared with values reported by Ben Ahmed et al (2009) in the same region, which could be attributed to harvest period, crop load and procedure of oil extraction.…”
Section: Discussioncontrasting
confidence: 69%
“…Indeed, with saline treatments a slight but not significant increase in oil content was observed (Klein et al, 1994;Gucci and Tattini, 1997;Wiesman et al, 2004). Saline treatments increase the levels of phenols and vitamin E in olive oil, while other oil composition parameters such as free fatty acids, peroxide value and fatty acid profile remained unaffected (Wiesman et al, 2004;Ben Ahmed et al, 2009;Stefanoudaki et al, 2009). Nevertheless, the long-term impact of irrigation regimes with saline water on olive growing has not yet been clearly studied.…”
Section: Introductionmentioning
confidence: 99%
“…These salts accumulation could be primarily due to high concentration of Na and Cl for both water resources. The alteration of plant growth, even at slight rate, such salinity levels could not be with a serious problem for Chemlali olive tree, at least under described environmental conditions as reported by Ben Ahmed et al (2009). The high Na concentration in soil solution can be explained by: (i) the antagonistic activity of either K + or NH 4 + which reduced the adsorption of Na on exchangeable complex and (ii) high calcium supply that enhanced the selectivity for the uptake and transport of K + over Na + .…”
Section: Soil Chemical Propertiesmentioning
confidence: 72%
“…Peroxide values, FFA values, and UV‐specific extinction coefficients were all found to be stable regardless of salinity . Nevertheless, fatty acid profile was reported to change significantly under induced salinity conditions . These changes, however, differed greatly among the studies, to an extent where no general statement can be made concerning characteristic tendencies.…”
Section: Introductionmentioning
confidence: 91%